In vitro Study of Bioﬁlm Sensitivity of to the Enzyme Complex Included in Wobenzym - K. V. Shalepo; E. V. Spasibova; O. V. Budilovskaya; A. A. Krysanova; T. A. Khusnutdinova; A. S. Cheberya; A. R. Cheberya; A. M. Savicheva (Антибиотики и Химиотерапия, 2024)
Background. Bacterial ﬁlms are a marker of chronic recurrent infections. Bioﬁlms on mucous membranes block the inﬂammatory response of the macroorganism, suppressing the activity of immunocytes, and thereby allow microorganisms to reach high concentrations. Currently, research is being conducted to ﬁnd medications that can act on bioﬁlms. Enzymes, especially their complexes, are substances that can destroy bacterial ﬁlms. Objective. Еo determine in vitro the sensitivity of bacterial bioﬁlms formed by vaginal microorganisms to the complex of enzymes included in Wobenzym. Materials and methods. The study included 72 clinical isolates of pure microorganism cultures isolated from the vaginal biotope: Gardnerella vaginalis (3), Enterococcus faecalis (9), Escherichia coli (18), Klebsiella pneumoniae (15), Klebsiella aerogenes (3), Lactobacillus crispatus (3), Streptococcus pyogenes (3), Acinetobacter baumanii (3), Staphylococcus aureus (3), Candida albicans (3), Enterococcus faecium (3), Streptococcus agalactiae (3), Lactobacillus acidophilus (3). Bacterial bioﬁlm formation was determined in polystyrene ﬂat-bottom plates using a modiﬁed method of Christensen et al. (1985). The tablet form of Wobenzym was used in the study. The tablet shell was washed with saline, the tablet itself was dissolved in 10 ml of 0.9% NaCl and used for in vitro studies. The result was determined using a reader on a spectrophotometer to determine the optical density (OD) of the formed bioﬁlm. It was believed that the drug acted on the bacterial ﬁlm, reducing the OD by more than three times. Results. An in vitro study revealed clinical isolates of bacteria that formed bioﬁlms of varying severity. Of the 72 clinical bacterial isolates, 38 formed bioﬁlms. A pronounced eﬀect of the complex of enzymes included in Wobenzym on bioﬁlms formed by microorganisms such as A. baumanii, S. aureus, G. vaginalis and E. faecalis was noted. Conclusion. Wobenzym has an eﬀective destructive eﬀect on bioﬁlms formed by various microorganisms, including G. vaginalis, common causative agents of bacterial vaginosis, as well as staphylococci and enterococci, causative agents of aerobic (nonspeciﬁc) vaginitis. Conclusion. The drug Wobenzym has an eﬀective destructive eﬀect on bioﬁlms formed by various microorganisms, including Gardnerella vaginalis, common causative agents of bacterial vaginosis, as well as staphylococci and enterococci, causative agents of aerobic (nonspeciﬁc vaginitis).